Aggregation-induced fluorescent response of urea-bearing polyphenyleneethynylenes toward anion sensing. Issue 1 (31st December 2021) - Li, Jian; Saleem, Muhammad; Duan, Qian; Kakuchi, Toyoji; Chen, Yougen
ABSTRACT: A π-conjugated urea-bearing phenyleneethynylene polymer (Poly-2 ) was rationally designed by the Sonogashira coupling condensation reaction and had been demonstrated to have a unique fluorescent quenching effect for the optical detection of all determined anions, especially for CN − . The fluorescent emission of Poly-2 was significantly quenched upon adding CN −, together accompanied with a continuous red shift of the emission peak from 442 to 464 nm with the cyanide concentration increased from 0 to 1.0 mM. On the contrary, its precursor polymer, Poly-1, itself also displayed fluorescent responsibility with all selected anions but had no obvious selectivity and tendency. For instance, the addition of highly basic CN −, N3 −, AcO −, or F − to Poly-1 solution in DMF/H2 O (v/v = 1:1) led to the photoluminescence amplification, while the addition of weakly basic anions like Cl −, I −, and Br − showed a fluorescence quenching effect. Both polymers were in a seriously self-aggregated state in solution no matter in the absence or presence of an anion. Interestingly, it was found that Poly-2 exhibited an aggregation-induced emission behavior, while Poly-1 had an aggregation-caused quenching effect, based on the relationship between photoluminescence and polymer aggregation state. The structural characterizations were carried out by NMR spectroscopy and size exclusion chromatography measurements; the photoluminescence properties of Poly-1 and Poly-2 together with anion sensing properties were followed by fluorescence spectroscopy, and the relationship between photoluminescence and aggregation behavior of both polymers in solution was investigated by dynamic light scattering measurements. Graphical abstract: uf0001